Representations of the real forms of calibrated analogue of the Lie algebra - Ostrovsky, V.L.; Silvestrov, S.D. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Real-valued forms of the ${\mathbb Z}_2^n$ -graded analogue of the Lie algebra $sl(2, {\mathbb C})$ are described and their irreducible representations are studied.